Efektivitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Terhadap Peningkatan Hasil Belajar Siswa Dalam Materi Bencana Angin Badai Dengan StrategiTwo-Stay Two-Stray Di SMK Negeri 1 Klaten - Nur Aliyah, Eka; , Dr. Tjipto Subadi,M.Si (2016)
The objectives of the research are to know:1) the effectiveness of the learning guide books disaster issued by BPBD Klaten district with a focus on disaster whirlwind material. 2) an increase in the acquisition of student learning outcomes with the implementation of the strategy Two-Stay-Two Stray in the learning process. The method used was experimental research with study design Nonequivalent Control Group Design, this design uses an experimental class and control class by comparing students' learning outcomes which have been given treatment and students who were not given the treatment. Classes are used as an experimental class is class X AP 2 totaling 31 students with the process of learning to use strategies Two-Stay-Two Stray and grade used as the control class is the class X AP 1 totaling 32 students using conventional methods. Data analysis technique used is Paired Sample t-Test to determine the level of difference in learning outcomes of students in the experimental class and control class. Based on the results of analysis show that student learning outcomes using the strategy Two-Stay-Two Stray increased more significantly by 22%, while the control class that uses the conventional method of learning outcome also increased by 16%. The result of the acquisition value of these students can be concluded that the use of teaching materials guide books disaster can be considered effective because it is able to improve student learning outcomes through strategies Two-Stay-Two Stray than using conventional methods. Keywords: Learning Materials, Learning Outcomes, Wind Storms, and Two-Stay-Two Stray.